1974
DOI: 10.1111/j.1399-0004.1974.tb01695.x
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal recessive Cerebro‐Oculo‐Facio‐Skeletal (COFS) syndrome

Abstract: Ten patients displaying a uniform Cerebro‐Oculo‐Facio‐Skeletal (COFS) syndrome are presented. The syndrome is characterized by microcephaly, hypotonia, microphthalmia, cataracts, blepharophimosis, large ear pinnae, prominent root of the nose, micrognathia, widely set nipples, camptodactyly, flexure contractures at the elbows and knees, generalized osteoporosis, dysplastic acetabula, coxa valga and vertical talus manifesting as rocker bottom feet. Marked failure to thrive and repeated lower respiratory infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(23 citation statements)
references
References 6 publications
1
22
0
Order By: Relevance
“…Cerebro-Oculo-Facio-Skeletal Syndrome (COFS) COFS was first described in 1974 (Pena and Shokeir 1974;Preus and Fraser 1974), with most of the features (microcephaly, hypotonia, failure to thrive, eye defects, prominent nose, large ears, micrognathia, kyphoscoliosis, and osteoporosis) rather similar to those observed among CS patients. Meira et al (2000) showed that three patients originally diagnosed as COFS show a CS-like cellular phenotype (UV hypersensitivity and defective recovery of RNA synthesis after UV).…”
Section: Cockayne Syndrome (Cs)mentioning
confidence: 99%
“…Cerebro-Oculo-Facio-Skeletal Syndrome (COFS) COFS was first described in 1974 (Pena and Shokeir 1974;Preus and Fraser 1974), with most of the features (microcephaly, hypotonia, failure to thrive, eye defects, prominent nose, large ears, micrognathia, kyphoscoliosis, and osteoporosis) rather similar to those observed among CS patients. Meira et al (2000) showed that three patients originally diagnosed as COFS show a CS-like cellular phenotype (UV hypersensitivity and defective recovery of RNA synthesis after UV).…”
Section: Cockayne Syndrome (Cs)mentioning
confidence: 99%
“…To our knowledge, only 14 cases (including our three cases), described as COFS syndrome by their authors, have been fully explained at the molecular level (table 1). 2 11 13 1620 23 Six out of these originate from the same Manitoba aboriginal population and are related to the same homozygous mutation in CSB . All these COFS patients have an identical DNA repair defect in the TCR subpathway, which is indistinguishable from the classical defect displayed by CS cells.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebro-oculo-facio-skeletal syndrome (COFS syndrome, MIM 214150) was first reported by Lowry in 19711 and officially delineated by Pena and Shokeir2 in 1974 within the Manitoba aboriginal population, as an autosomal recessive disorder defined by microcephaly, cataracts, microphthalmia, facial dysmorphism and arthrogryposis. From the earliest reports, there appeared to be considerable heterogeneity among the reported cases of COFS syndrome and confusing clinical overlaps between COFS syndrome and other autosomal recessive eye and brain disorders such as MICRO syndrome (MIM 600118) or Martsolf syndrome (MIM 212720) 19…”
mentioning
confidence: 99%
“…One can further subdivide CS patients into three groups: type I, the classical CS described above; type II, a very severe form, with major neurological symptoms, generally lethal in infancy; and a milder form of the disease [84,85]. There also exists a clinical entity known as COFS (cerebro-occulo-facio-skeletal syndrome, sometimes called Pena-Shokeir type II syndrome), which is closely related to CS [86,87]. The clinical presentation is reminiscent of that of CS, with growth retardation, severe neurological symptoms, ocular abnormalities, and progressive joint contractures, but it also comprises symptoms rarely observed in classical CS, such as horseshoe kidneys and other visceral anomalies.…”
Section: Cockayne Syndromementioning
confidence: 99%